Photosynthesis, Pigment–Protein Complexes and Electronic Energy Transport: Simple Models for Complicated Processes. (September 2017) - Baker, Lewis A.; Habershon, Scott
In this review, we discuss our recent work on modelling biological pigment–protein complexes, such as the Fenna–Matthews–Olson complex and light-harvesting complex-II, to explain their electronic energy transport properties. In particular, we highlight how a network-based analysis approach, where the light-absorbing pigments are treated as a network of interconnected nodes, can provide a qualitative picture of quantum dynamic energy transport. With this in mind, we demonstrate how other properties such as robustness to environmental changes can be assessed in a simple and computationally tractable manner. Such analyses could prove useful for the design of artificial energy transport networks such as those which might find application in solar cells.